Relation of riverbank erosion with land use practices on floodplain of Weyb River at Agarfa District villages, south east Ethiopia - Abdela, Umer; Shiferaw, Dinku; Abdulsemed, Seifeden; Seid, Mehasin (Frontiers in Environmental Science, 2025)
The relationship between riverbank erosion and land use practices is a critical issue that impacting developing and developed nations and recognized as a significant environmental challenge, with human activities exacerbating it. In the same way, the floodplain of Weyb River in Agarfa district villages in southeast Ethiopia is confronting a significant challenge due to escalating riverbank erosion, posing a threat to the sustainability of this critical ecosystem. The findings from this study aim to evaluate the dynamics of riverbank erosion with land use practices and inform policymakers and stakeholders about the critical need for sustainable land use practices that mitigate erosion and enhance the resilience of affected communities. The study employed a mixed-methods approach, integrating quantitative and qualitative data collection techniques through field observations, community surveys and land-use land cover change analysis, this study has uncovered key insights into the complex relationship between land-use practices and erosion dynamics. Notably, the research identified significant erosion hotspots in villages such as Ambentu villages, Koloba Seada, and Harogoda, where 96.5% of respondents recognize drainage congestion along the river necessitating the operation of sluices. Moreover, Analysis reveals the intricate interplay between human activities and erosion dynamics. The study revealed critical causes of riverbank erosion, including excessive flooding and heavy rainfall upstream, and poor land cover along the riverbanks. Respondents identified that farming practices, particularly removing vegetation and farming near the riverbank, significantly contribute to erosion. Additionally, 92% of key informants agreed that agricultural activities such as seedlings rising near the river exacerbate erosion risks. The study recommends the development of river buffer zones, establishment of community conservation associations, implementation of riverbank rehabilitation measures, infrastructure development, community support and empowerment, deployment of developmental agents, and strengthening community adaptation to flood hazards. Urgent action is crucial to safeguard the Weyb River floodplain ecosystem and ensure long-term sustainability amid ongoing ecological changes and human interventions.